Ultra Fast Switching of DFLC Based Dynamic Metasurfaces - Sakhare, P. A.; Dontabhaktuni, Jayasri (Frontiers in Physics, 2022)
Dielectric metasurfaces give rise to very interesting optical and photonic properties such as Huygens lens, absolute transmission and absorption, directional scattering, etc. Liquid crystal based dynamic metasurfaces are being increasingly explored due to their excellent tunability of polarization, phase and amplitude modulations, enabling applications in spatial light modulators (SLM’s), holography, AR and VR and flat optics. We investigate the effect of geometry of dielectric microstructures on electromagnetic response and switching of Dual frequency liquid crystal based metasurfaces in the mid-IR range of frequencies. Scattering response, near-field profiles and far-field radiation show significant dependence on the alignment and geometry of the microstructures. At selected frequencies switching between different polarization directions and variable phase modulations are observed simultaneously. Response times calculated theoretically show switching times of the order of milliseconds paving way for ultrafast multifunctional active metasurfaces.